Progressive multifocal leukoencephalopathy: rheumatological aspects - Boris Sergeevich Belov (Современная ревматология, 2015)
Progressive multifocal leukoencephalopathy (PML) is a severe progressive viral disease that affects the central nervous system in patients with immunodeficiency. It may develop as a complication in patients with systemic inflammatory rheumatic diseases (primarily in those with systemic lupus erythematosus), including that during active antirheumatic therapy. The paper presents data on the etiology, epidemiology, and pathogenesis of the disease, characterizes its clinical presentation, highlights main approaches to its diagnosis, and gives current diagnostic criteria. A questionnaire used to monitor neurological status is shown. The paper emphasizes the importance of this monitoring, for early diagnosis and timely cessation of PML treatment with a drug, a potential trigger, are factors that influence prognosis to the utmost degree.